(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The study estimated short and long run relationships between trade liberalization and agricultural export performance in Nigeria from 1999-2020. Time series analytical were used. Result revealed that, two variables; agricultural import (AIMP) and agricultural degree of openness (ADO) were stationary at levels while others; (ACF, AEXP, EXR and NAP) became stationary at first difference. The short-run and long-run agricultural GDP performance with respect to the macro-economic variables were analysed using the techniques of co-integration and error correction models. Result revealed that,at the long run, coefficients of agricultural export (AEX), agricultural degree of openness (ADO), national agricultural productivity (NAP) and agricultural capital formation (ACF) were positively significant at 1 and 10 percent levels respectively. Agricultural import (AIMP) and exchange rate (EXR) were negative but significant at 1 and 5% respectively. At the short-run, result shows a negative but significant relationship with respect to agricultural capital formation (ACF), agricultural export (AEXP) and exchange rate (EXR. Result revealed negative relationship between national agricultural productivity (NAP), exchange rate (EXR), agricultural import (AIMP), agricultural export (AEXP) and agricultural capital formation (ACF) at one year lagged. With R2-adjusted of 0.9273 and ECM of -0.6372 implies that, 92.73% variations in Agricultural GDP performance was affected by the independent variables and 63.72 of disequilibrium in the current period may be corrected for in the long-run. The study recommended that, appropriate short- and long-term economic policy instruments should be enforced to stimulate investment and production opportunities in the agricultural sector so as to increase agricultural GDP performance.